STUDI VARIASI PERMUKAAN LAUT JAWA DAN LAUT CHINA SELATAN TAHUN 2002-2019 MENGGUNAKAN DATA ALTIMETRI JASON - Sulaiha, Fiamanati; Handoko, Eko Yuli; Yuwono, Yuwono (Geoid, 2020)
The phenomenon of global warming can lead to thermal exposure and variations in water masses that require melting glaciers, polar ice sheets and changes in global sea level averages. This effect has an important impact on socio-economic, infrastructure and environment, which causes land changes of around 10% of the world's population. Since the end of the 18th century, changes in the position of open air from tidal stations along the coastline. However, observation of tide stations has limitations in number, distribution, and coverage, as well as variations in land subsidence. Therefore, this study analyzes sea surface variations in the Java Sea and the South China Sea during the period 2002-2019 using altimetry satellite reference mission data, namely Jason 1, Jason 2, and Jason 3. Sea level variations that need to be studied increase sea air by 4.1 mm/year, where high speeds occur around the North or South Java Sea which has a value of 7-9 mm / year. So based on these results pre-event planning can be carried out on the impact of the upcoming sea level rise.